A systematic review: Cost‐effectiveness of continuous glucose monitoring compared to self‐monitoring of blood glucose in type 1 diabetes. Issue 6 (16th September 2022) - Jiao, Yuxin; Lin, Rose; Hua, Xinyang; Churilov, Leonid; Gaca, Michele J.; James, Steven; Clarke, Philip M.; O'Neal, David; Ekinci, Elif I.
Abstract: Continuous glucose monitoring (CGM) is rapidly becoming a vital tool in the management of type 1 diabetes. Its use has been shown to improve glycaemic management and reduce the risk of hypoglycaemic events. The cost of CGM remains a barrier to its widespread application. We aimed to identify and synthesize evidence about the cost‐effectiveness of utilizing CGM in patients with type 1 diabetes. Studies were identified from MEDLINE, Embase and Cochrane Library from January 2010 to February 2022. Those that assessed the cost‐effectiveness of CGM compared to self‐monitored blood glucose (SMBG) in patients with type 1 diabetes and reported lifetime incremental cost‐effectiveness ratio (ICER) were included. Studies on critically ill or pregnant patients were excluded. Nineteen studies were identified. Most studies compared continuous subcutaneous insulin infusion and SMBG to a sensor‐augmented pump (SAP). The estimated ICER range was [18, 734–99, 941] and the quality‐adjusted life year (QALY) gain range was [0.76–2.99]. Use in patients with suboptimal management or greater hypoglycaemic risk revealed more homogenous results and lower ICERs. Limited studies assessed CGM in the context of multiple daily injections (MDI) ( n = 4), MDI and SMBG versus SAP ( n = 2) and three studies included hybrid closed‐loop systems. Most studies ( n = 17) concluded that CGM is a cost‐effective tool. This systematic review suggests that CGM appears to be a cost‐effective tool for individuals with type 1 diabetes. Cost‐effectiveness is driven by reducing short‐ and long‐term complications. Use in patients with suboptimal management or at risk of severe hypoglycaemia is most cost‐effective. Abstract : Continuous glucose monitoring has advanced significantly in the last few years. Multiple studies and meta‐analysis have reported the benefit of continuous glucose monitoring in improving diabetes management and hypoglycemic risk. Cost has however remained a barrier to its widespread use. This review summarises available studies assessing the cost‐effectiveness of CGM.